Innovative Strategy in Marketing Beauty Products Through TikTok Affiliates in Tangerang Regency - Mutiara, Afifah; Suwarno; Ratna Sari, Yuni; Mahmud, Imam (Talenta Publisher, 2025)
This research examines the meaning of symbolic interactionism in beauty affiliate marketing strategies on the TikTok application. TikTok has evolved into a major platform for marketing, as the digital ecosystem evolves. TikTok affiliates serve as intermediaries between brands and customers by using symbols to build product perceptions. The purpose of this study is to find out how TikTok affiliates in Tangerang Regency use communication symbols such as hashtags, facial expressions, body language, speaking styles through digital trends and following the TikTok algorithm to create an image of beauty products and attract audiences. This research uses a qualitative research method with a phenomenological approach. Data were collected through interviews, observations and documentation listed to verify the truth of the data obtained. The results of this study show that affiliates not only promote products, but also create meaning through social interaction with the audience. Affiliates can increase audience engagement by sharing personal experiences, using hooks, CTAs, thumbnails, providing honest reviews. Affiliates can also increase their credibility by using TikTok features such as FYP and yellow baskets. Thus, this study provides an understanding of the role of TikTok social media in digital marketing and offers a new perspective for affiliates and brands in developing strategies about marketing beauty products on TikTok.Keywords: Tiktok, Affiliate Program, Strategic Marketing, Personal Branding